Strategic Tax Competition with a Mobile Population - Fernández, Gonzalo E. (2002)
This paper analyzes a model of strategic tax competition with mobile capital and mobile identical consumers. The results of the model are compared to the traditional strategic tax competition model with immobile population. In addition to the fiscal and pecuniary externalities present in the standard model, a new effect shows up in the mobility model to affect provision of the public good. As with the pecuniary externality, this new effect depends on whether the jurisdictions are net exporters or net importers of capital. Thus, in a symmetric set up, the mobility effect along with the pecuniary externality disappear, yielding unambiguous underprovision of the public good. While in the asymmetric case both models have the same qualitative results, the mobility model strengthens the effects of the pecuniary externality. The above results are obtained by comparing the form of the first-order conditions between the mobility and immobility cases. The remaining question is whether or not the equilibrium levels of the public goods conform to the predicted tendencies. This question is answered with an example. The results of this exercise show that when the jurisdiction is a net exporter of capital, the level of the public good is lower in the mobility case than in the immobility case. However, if the jurisdiction is a net importer of capital, the public good level is sometimes higher and sometimes lower in the mobility case, contrary to predictions.